JURNAL KESEHATAN JURNAL ILMU KESEHATAN STIKES DUTA GAMA KLATEN - Putri Kusumawati Priyono (STIKES DUTAGAMA KLATEN, 2021)
The use of contraceptives is in the spotlight, especially during the COVID-19 pandemic. COVID-19 has now been declared a global health emergency. The Indonesian government also had time to implement Large-Scale Social Restrictions to break the chain of transmission of this virus. This has an impact on various health sectors, especially reproductive health. Contraceptive services are neglected due to social restrictions, mothers are forced to not be able to consult doctors and to puskesmas to get contraceptive services, even Indonesia is predicted to experience a baby boom because all activities are carried out at home. For this reason, this study aims to analyze the use of contraceptives during the COVID-19 pandemic by using the literature review method to identify all published literature with relevant keywords. Based on the results of a literature review, the pandemic situation forces health services to focus their services on handling COVID-19, causing low contraceptive services as well as limitations on service hours which have an impact on the lack of health workers serve family planning services